Scientific and Artful Voices of Resilience - Devchand, Pallavi R. (Frontiers in Pharmacology, 2021)
Resilience is a fluid trait that is triggered by personal experience. It is, arguably, a necessity for a scientist. What is it? You know it, when you see it. One thing is for certain: resilience reflects the dynamic toggle between change and an individual’s identity.